Fluoroscopy-induced chronic radiodermatitis: three cases presenting after cardiac catheterization - Galal El-Enany; Khaled El Hoshy; Randa Youssef; Noha Nagui; Hanan Nada; Mona Abdel Halim; Ahmed Nada; Dina Elantably; Iman Sany (Wolters Kluwer Medknow Publications, 2021)
Fluoroscopy-induced chronic radiodermatitis is a rare complication that is now encountered more often owing to the increasing use of fluoroscopy in radiological procedures. The long duration between radiation exposure and development of condition, patient unawareness of exposure to radiation along with lack of clinical suspicion of the condition among dermatologists, all make the diagnosis difficult. We report three cases of male patients who presented with a clinical picture suggestive of fluoroscopy-induced chronic radiodermatitis backed up by history of cardiac catheterization procedures confirming the diagnosis. Awareness of this entity among dermatologists is important for early recognition and proper management.